Die kleine Hexe - Preußler, Otfried,Bödecker, Hans,Gebhardt-Gayler, Winnie (Schroedel, 1963)
Unfortunately, the little witch is only 127 years old and is therefore not taken seriously, so she tries to be a good witch and confusion follows.
Keywords: Kinderbuch; Deutsch; Fairy tales; German language; Witches; Hilfsbereitschaft; Hexe